2002
DOI: 10.1007/s00412-001-0179-8
|View full text |Cite
|
Sign up to set email alerts
|

Intranuclear relocation of the Plc β 3 sequence in cerebellar Purkinje neurons: temporal association with de novo expression during development

Abstract: Interphase nuclei exhibit a cell type-specific topology of chromatin domains. This topology has been proposed to be established at a specific developmental stage and to be associated, in turn, with cell type-specific gene expression. Using murine, cerebellar Purkinje neurons, we have shown previously that the number and the extent of clustering as well as the spatial, intranuclear distribution of centromeric domains change as a function of postnatal development. Specifically, the redistribution of centromeric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
(47 reference statements)
1
7
0
Order By: Relevance
“…The distinct centromere proximity pattern of chromosomes 2 and 11 in Purkinje and granule neurons may indicate specific roles of these centromeres for neuron-specific function. The structural association of centromeres in Purkinje neurons may be associated with the de novo expression of specific gene sequences, as shown previously (Martou et al 2002). This also supports the concept that the centromeres of chromosomes may be sufficiently unique, as previously hypothesized (Karpen and Allshire 1997), and may indicate that these differences are recognized during the chromosomespecific formation of centromeres.…”
Section: Spatial Distribution Of Neuronal Centromeressupporting
confidence: 69%
See 1 more Smart Citation
“…The distinct centromere proximity pattern of chromosomes 2 and 11 in Purkinje and granule neurons may indicate specific roles of these centromeres for neuron-specific function. The structural association of centromeres in Purkinje neurons may be associated with the de novo expression of specific gene sequences, as shown previously (Martou et al 2002). This also supports the concept that the centromeres of chromosomes may be sufficiently unique, as previously hypothesized (Karpen and Allshire 1997), and may indicate that these differences are recognized during the chromosomespecific formation of centromeres.…”
Section: Spatial Distribution Of Neuronal Centromeressupporting
confidence: 69%
“…Fluorescence in situ hybridization (FISH) studies showed that the Purkinje-neuron-specific Plcβ3 sequence is relocated within the nuclear space, temporally coincident with its de novo expression. In contrast, Rorα, a sequence that is not expressed during the same time frame, did not alter its spatial intranuclear position (Martou et al 2002). However, studies of the relative positioning between centromeric domains in neurons have not been reported.…”
Section: Introductionmentioning
confidence: 92%
“…Individual chromosomes and gene loci have been shown to change their nuclear location upon stimuli, whether that be stimuli to induce differentiation [11,[33][34][35][36], signals that change growth status [10,37,38], environmental stimuli [12] or compounds to induce exogenous gene expression [39]. The consensus hypothesis in the field is that whole chromosomes are moved to allow some control over genes that are housed upon that chromosome, whether for expression or for repression.…”
Section: Repositioning Of Gene Loci and Whole Chromosomesmentioning
confidence: 99%
“…Enhanced synaptic input certainly means increasing physiological activity of the developing PCs involving active transcription of PC-specific genes. Martou et al (2002) described an example of intranuclear sequence relocation correlated with onset of gene expression by showing radial relocation of the Plcß3 gene between P3 and P5 coincident with its de novo expression between P2 and P7. Whether changes in higher-order chromatin arrangements in postmitotic PCs during the postnatal development of the cerebellum are a causal necessity or a consequence of changes of the gene expression pattern remains an intriguing question.…”
Section: Changes Of Nuclear Architecture During Terminal Pc Differentmentioning
confidence: 99%